The reader's brain : how neuroscience can make you a better writer - Douglas, J. Yellowlees, 1962- (Cambridge : Cambridge University Press, 2015)
Have you ever found yourself re-reading the same sentence four or five times and thought'I should get more sleep'? Are you clueless as to why one paragraph just seems to'flow' while you simply can't recall the contents of another? Guess what: you are not alone. Even the best writers fail to grasp why their writing works. The Reader's Brain is the first science-based guide to writing, employing cutting-edge research on how our minds process written language, to ensure your writing can be read quickly, assimilated easily, and recalled precisely - exactly what we need to transform anyone into a highly effective writer. Using the 5Cs - clarity, continuity, coherence, concision, and cadence - this book combines irreverent humour with easy-to-follow principles that will make readers perceive your sentences, paragraphs, and documents to be clear, concise, and effective.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Reading -- Psychology